Application of PN Code in Time Delay Measurement of Telephone Network - Xiaozhen Jin; Yu Hua (Sensors)
Telephone time service is a wired time service that transmits time signals through a telephone network, with the advantages of simple receiving equipment and wide coverage. But the performance of time service is not high, usually several milliseconds. The time delay measurement of the telephone network is an important factor limiting the improvement in timing performance. The existing telephone service systems measure time delay based on sending characters. The time fluctuation of modulating and demodulating characters and the low accuracy of detecting characters affect the uncertainty of time delay measurement. This article proposes a time delay measurement method based on sending PN codes. It utilizes the good autocorrelation properties of PN codes to improve detection accuracy and then improve the uncertainty of delay measurement. This article studies and designs the modulation, demodulation, and capture of PN codes. Simulation has verified that this method has strong anti-noise performance. Time delay tests have proved that this method can improve the uncertainty of delay measurement by an order of magnitude in different telephone network environments.